Kandungan Karbohidrat, Lemak Dan Kalsium Kulit Buah Pisang Ambon Kuning (Musa paradisiaca var. sapientum (L.) Kunt) Pada Dataran Tinggi Dan Dataran Rendah Di Kecamatan Leitimur Selatan Kota Ambon - Wakano, Deli; Killay, Amos; Caling, Wulandary Rasia (INSTITUT AGAMA ISLAM NEGERI AMBON, 2021)
The aim of this research is to find out the carbohydrate, fat, and calsium content of yellow Ambon banana (Musa paradisiaca var. Sapientum (L.) kunt) grown on South Leitimur lowland and highland, Ambon (as an attempt to convert banana peel into food). The research is a descriptive quantitative research. The research was conducted in Ambon Research and Standardization Center Laboratory on November 2016. The research measures physical and chemical factors such as height, soil pH, soil types, and temperature. Banana peels used in the research were taken from yellow ambon banana grown in two different areas: the lowland and the highland. The result shows that banana peels from the highland contain 4.07% carbohydrate, fat 0.82% and calcium 19.11 µg/gr, while banana peels from the lowland contain 4.08%, fat 0.85% and ca;cium 42.82 µg/gr. Keywords: Carbohydrate, fat, calcium, banana peel, yellow ambon banana, highland, lowland